Performance analysis of a novel outer rotor flux‐switching permanent magnet machine as motor/generator for vehicular and aircraft applications. Issue 2 (21st January 2021) - Sharouni, Sahar; Naderi, Peyman; Hedayati, Mahdi; Hajihosseini, Payman
Abstract: Herein, a novel study on outer rotor flux‐switching permanent magnet (OR‐FSPM) machines for motor/generator applications is presented. An improved magnetic equivalent circuit (MEC) is used for saturable machine model, and the performance analysis is presented in both dynamic and steady‐state cases. A flexible MEC‐based method is used, where the machines with arbitrary properties can be analysed. Moreover, the model accuracy can be tuned by selective parameters in the proposed method. It is shown that the machine can be used as a high efficiency 400 Hz Ground Power Unit (GPU) for aircraft application. Furthermore, the machine usage for in‐wheel application in the hybrid and electric vehicles (HVs and EVs) is analysed. Comparison with 2D and 3D finite‐element‐method (FEM) shows the effectiveness and accuracy of the proposed MEC method, where shorter processing time is obtained compared with FEM.